How to analyze a bank statement : a detailed guide to the financial statements of banks and bank holding companies - Garcia, F. L. (Boston : Bankers Pub. Co., 1974)
This edition devotes all of Part I to the reporting requirements, details of illustrative data reported, and suggested analytical techniques for analysis of bank holding company data. Part II updates exposition and data, as well as suggested analytical techniques, for analysis of commercial banks contained in previous editions.
Includes bibliographical references p.265-267.
hza 19/09/2018
Loans
Keywords: Banks and banking